OBSTETRICAL AND NEONATAL OUTCOMES AMONG PREGNANCIES COMPLICATED BY HYPERPARATHYROIDISM: SYSTEMATIC REVIEW - Sihotang, Samuel Halason; Sianturi, Prince (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Primary hyperparathyroidism (PHPT) is a relatively common disorder of the parathyroid glands, causing skeletal, renal, and cardiac complications. As etiological features of PHPT, single adenoma, hyperplasia, carcinoma, and familiar causes (MEN multiple endocrine neoplasia, FHH familiar hypocalciuric hypercalcemia, hyperparathyroidismjaw tumor syndrome) are presented. Primary hyperparathyroidism in pregnancy has an incidence of 1, which is underestimated due to the plethora of undiagnosed cases. The aim: This study aims to show about obstetrical and neonatal outcomes among pregnancies complicated by hyperparathyroidism. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 10 articles, whereas the results of our search on SagePub brought up 60 articles. The results of the search conducted for the last year of 2013 yielded a total 2 articles for PubMed and 14 articles for SagePub. The result from title screening, a total 1 articles for PubMed and 10 articles for SagePub. In the end, we compiled a total of 7 papers. We included five research that met the criteria. Conclusion: Pregnancy complicated by PHPT may lead to serious maternal and infant complications. MDT consultation ensures timely diagnosis, comprehensive treatment for the patients and better pregnancy outcomes.